Protecting Online Privacy by Heightening Communication Path Using Different Hops Path Tor - Saad, Amna; Roshidi Amran, Ahmad; Mohamed Fadli, Awang (International Journal of Engineering and Technology, 2018)
The vulnerabilities within the internet cause unauthorized person to hack and steal our private data and spot our location within the cyber world. Some people do not think this as an issue. They would be more upset if the link is down, the connection is slow or when the link is intermittent. Hence, without their knowledge, their well- being is being monitored by an unknown person or group. The in- formation gained can later be used against their personal interests. Others are very concerned about this matter. They want to protect their privacy and identity in the cyber world. We proposed a solution to curb these activities by providing extra layers of internet connectivity protection, in order to create anonymous communication on demand. In this project we develop two, three and six hops security of the Tor wireless router on a Raspberry Pi 3. The client can choose to use, either hardware based 3-hops path standard security Tor or software based security Tor custom for 2-hops and 6-hops paths via application software rebuilding using MSYS2 and MNGW tool. Our result shows that there is no significant performance different in term of the connections response time regardless of the number of the Tor path lengths.Â Â